تأثير التمارين مركبة لتطوير بعض الاداءات المهارية المركبة للاعبي كرة القدم بأعمار (16-14) سنة - فتاح, المشرف / أ.م.د.نەبەز عبدالله; حمدامین, الباحث / داماو رۆستەم (Sulaimani Journal for Humanities, 2023)
Compound exercises are one of the most important exercises of the game that works to develop the skill side of the football player, as it is similar to the player’s duty in the conditions of competitions, and combines more than one skill in one exercise, and also performs during the different stages of preparation as well as its diversity, which helps to increase the elements of desire and suspense when practicing it, Compound skill performances are a form of construction consisting of several interconnected skills that mutually affect each other to achieve a specific motor act. These compound skills usually arise from the link between the parts and stages of motor performance and their relationship among them to form the so-called compound skill performance. The aim of this research is to reveal the differences between the pre and posttests of the experimental group in the effect of compound exercises in developing a number of complex skill performance on the differences between the two tests before and after the control group of the effect of the approach in developing a number of complex skill performance on the differences between the two tests The dimension of the experimental and control group on the effect of vehicle exercises on the skill performance of the complex. The research procedures are as follows: The research methodology and its field procedures included, the researcher used the experimental method appropriate to the nature of the research, as the research sample was chosen in a deliberate way, and they are (24) players, the experimental group numbered (12) and the control group numbered (12) players, the results were presented, analyzed and then discussed: It included a presentation of the research results, after which the researcher analyzed and discussed the results that he obtained as a result of the tests he performed. The most important conclusions: Compound exercises have a positive effect in the development of some complex skills (receiving then scoring, receiving then running then dribbling then passing, receiving then running then scoring, receiving then dribbling and then scoring), and there is a clear discrepancy between the experimental and control group in the post test in The tests((receiving then scoring, receiving then running, then dribbling and then passing, Receiving, then running, then scoring, receiving, then dribbling, then scoring).